2015
DOI: 10.3390/children2010001
|View full text |Cite
|
Sign up to set email alerts
|

Impairments that Influence Physical Function among Survivors of Childhood Cancer

Abstract: Children treated for cancer are at increased risk of developing chronic health conditions, some of which may manifest during or soon after treatment while others emerge many years after therapy. These health problems may limit physical performance and functional capacity, interfering with participation in work, social, and recreational activities. In this review, we discuss treatment-induced impairments in the endocrine, musculoskeletal, neurological, and cardiopulmonary systems and their influence on mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 315 publications
(378 reference statements)
1
35
0
11
Order By: Relevance
“…Previous studies have demonstrated a significant reduction in stature of childhood cancer survivors (CCS), with multiple contributing factors suggested, including underlying diagnosis, age of diagnosis, cranial and spinal radiation, and a dose of radiation, as recently reviewed . The data from our study confirms a significant decrease in overall stature among CCS as well as a disproportionately greater deficit in thoracic than appendicular growth (ie, reduction in USL:SH ratio), as previously reported in children with leukemia and Wilms’ tumor .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have demonstrated a significant reduction in stature of childhood cancer survivors (CCS), with multiple contributing factors suggested, including underlying diagnosis, age of diagnosis, cranial and spinal radiation, and a dose of radiation, as recently reviewed . The data from our study confirms a significant decrease in overall stature among CCS as well as a disproportionately greater deficit in thoracic than appendicular growth (ie, reduction in USL:SH ratio), as previously reported in children with leukemia and Wilms’ tumor .…”
Section: Discussionsupporting
confidence: 88%
“…This disparity may also reflect differences in treatment regimens as participants treated during childhood would have received treatment in an earlier era when the dose of anthracyclines and the prevalence of mantle field radiation were higher compared to more recent eras . Cancer treatment could also indirectly affect the risk of cardiovascular disease mortality by impacting various behavioral and psychosocial determinants of health . These indirect pathways may play a lesser role in mediating the relation between lymphoma treatment and cardiovascular disease risk among those treated later in life which could partially account for this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…81 Cancer treatment could also indirectly affect the risk of cardiovascular disease mortality by impacting various behavioral and psychosocial determinants of health. 82,83 These indirect pathways may play a lesser role in mediating the relation between lymphoma treatment and cardiovascular disease risk among those treated later in life which could partially account for this heterogeneity. Regardless of the underlying mechanism, our results suggest that childhood Hodgkin lymphoma survivors are a population with a particularly high risk of experiencing a fatal cardiovascular event.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic procedures are questioned due to the long-term implications for the children whose skeleton is growing. On the other hand, osteonecrosis occurs rarely in solid tumors 6 . 2.…”
Section: Early Effectsmentioning
confidence: 99%